The tadpoles of Murree Hills Frog Nanorana vicina (Anura: Dicroglossidae) - Gill, Sumbul; Rais, Muhammad; Saeed, Muhammad; Ahmed, Waseem; Akram, Ayesha (Zootaxa, 2020)
The genus Nanorana, also called Yunnan Slow Frogs (Frank & Ramus 1995), belongs to the family Dicroglossidae. Murree Hills Frog N. vicina, is an endemic species of Southeast Asian uplands in Pakistan and India and was first reported by Stoliczka (1872) from Murree, Punjab Province, Pakistan. Later Rais et al. (2014) recaptured it from its type locality and described morphology of one juvenile female and one adult male. The species is listed as Least Concern in IUCN Red List of Threatened Species while the EDGE (Evolutionarily Distinct and Globally Endangered) score is 2.64. In Pakistan, it is reported from brook water springs and streams of Murree, Galiat (North Punjab), Ayubia (Khyber Pakhtunkhwa), and parts of Azad Jammu and Kashmir (Rais et al. 2014). Although the adult form has been characterized (Khan 2006; Rais et al. 2014), the morphology of the tadpoles have not yet been described. The current study aimed to describe external morphology and morphometry of tadpoles of N. vicina.